What Would You Do? Types of Ethical Challenging Situations Depicted in Vignettes Published in the Veterinary Literature from 1990 to 2020 - Anne Quain; Michael P. Ward; Siobhan Mullan (Veterinary Sciences, 2021)
Veterinary team members encounter a wide range of ethically challenging situations (ECS) in their work. Inability to resolve ECS in accordance with their values may negatively impact the wellbeing of veterinary team members. We sought to determine the types of ECS described in published ethical vignettes in the veterinary literature. We performed a strategic literature search, followed by a thematic analysis of vignettes published in the veterinary literature from 1990–2020. We identified 567 published vignettes in 544 publications. In the majority of vignettes, the protagonist was a veterinarian (61.6%) and the most common categories of animal involved were dogs (28.0%), livestock in general (10.8%), and cattle (10.6%). The primary type of ECS was coded for each scenario, generating 29 themes. These findings extend knowledge about types of ECS that may be encountered by veterinary team members. These themes can help to inform curricula and better prepare veterinary team members to navigate ECS. They may also highlight factors that contribute to ECS that can be addressed on a broad scale, such as through regulation, continuing professional development, or stakeholder education. Knowing that others may experience similar ECS may help veterinary team members feel part of a moral community.